2020
DOI: 10.3390/w12020441
|View full text |Cite
|
Sign up to set email alerts
|

The Migration Law of Iron during the Process of Water Icing

Abstract: In this study, we utilized simulated icing experiments to investigate the effect of icing thickness, freezing temperature and initial concentration on the migration of iron in the ice–water system during water icing. The distribution coefficient “K” (the ratio of the average concentration of iron in the ice to that in the under-ice water) was used to describe the effect. The results indicated that iron partitioned stronger to under-ice water than to ice during the process of water icing, resulting in the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Driven by the concentration gradient, vertical convection is generated in the water beneath the ice [ 40 ]. In straightforward terms, atrazine is repelled by the ice and migrates toward the bottom (i.e., the lower concentration region) during the crystallization of water molecules [ 41 , 42 ]. In addition, as the energy of the system decreases, the energy difference between the solute and the water and ice molecules drives the migration of the solute from the unstable ice phase to the stable water phase [ 14 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Driven by the concentration gradient, vertical convection is generated in the water beneath the ice [ 40 ]. In straightforward terms, atrazine is repelled by the ice and migrates toward the bottom (i.e., the lower concentration region) during the crystallization of water molecules [ 41 , 42 ]. In addition, as the energy of the system decreases, the energy difference between the solute and the water and ice molecules drives the migration of the solute from the unstable ice phase to the stable water phase [ 14 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The migration ability of atrazine in ice-water phases is affected by factors including ice thickness, freezing temperature, and atrazine initial concentration [ 42 ]. During the freezing process, as temperature decreases, ice crystals gradually grow and form ice cover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The atrazine concentration in ice increases as the solution concentration increases [39]. However, although the amount of captured atrazine in ice increases, it is more advantageous for atrazine to migrate to water under ice during the freezing process, the increase in atrazine concentration in ice at various concentrations was less than the migration [40]. Therefore, the K value of atrazine decreases with an increase in the initial concentration, and the migration ability of atrazine from ice to water under ice increases.…”
Section: In Uence Of Various Factors On the Migration Capacity Of Atrazinementioning
confidence: 99%
“…Laboratory experiments by Tang et al (2020) indicated that iron partitioned at a greater rate into the under-ice water rather than the freezing ice during the water freezing process. The partition coefficient decreases with the increase in ice thickness, initial concentration, and freezing temperature [ 15 ]. Both the conclusions of Sun et al (2018) and Tang et al (2020) are based on the freshwater experiments, and the metals are of a pure ionic state.…”
Section: Introductionmentioning
confidence: 99%